The Effect of Storytelling on the Motivation to Perform Personal Hygiene in Preschool-Aged Children in Mandala Kumara Denpasar Kindergarten - Luh Pt Juniari Listuayu (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Motivation to perform personal hygiene in preschool children is a encouragement to perform self-care to maintain their physical and psychological health. In the preschool periods, children are more focused to the playing world that leads to reluctance in performing personal hygiene. Child's health behaviors can be influenced by the their knowledge. Storytelling has become one of the effective solutions to give health education to preschool children because children's cognitive development is imaginative and full of fantasies. The aim of this study is to determine the effect of storytelling on the motivation to perform personal hygiene in preschool children in Mandala Kumara Denpasar kindergarten. This study is a pre-experimental study (one-group pre-post-test design without control group). Sample consisted of 37 preschool children obtained from total sampling. The data was collected by using questionnaires which has been designed tested for their validity and reliability. All respondents had been given storytellings with personal hygiene-theme using dolls as media for 12 sessions in a row with duration of 15-30 minutes. Respondent motivation levels were measured using pre-test and post-test questionnaires which were filled by the parents of respondents. The results obtained were 20 children (54.1%) with high motivation level, 16 children (43.2%) with medium motivation level, and 1 child (2.7%) with low motivation level to perform personal hygiene before being given storytelling. After being given storytelling, all 37 children (100%) have increased in motivation to the high motivation level. Based on the Wilcoxon Signed Rank Test, this difference was statistically significant, with ??asymp sig value (2-tailed) of 0.000, which means there is an influence of storytelling to the motivation to perform personal hygiene in preschool children in Mandala Kumara Denpasar kindergarten.